2021
DOI: 10.3390/ijms222011057
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell-Dependent Antibody-Mediated Immunotherapy Is Improved In Vitro and In Vivo When Combined with Agonists for Toll-like Receptor 2 in Head and Neck Cancer Models

Abstract: The immunosuppressive character of head and neck cancers may explain the relatively low response rates to antibody therapy targeting a tumor antigen, such as cetuximab, and anti-PD-1 checkpoint inhibition. Immunostimulatory agents that overcome tumor-derived inhibitory signals could augment therapeutic efficacy, thereby enhancing tumor elimination and improving patient survival. Here, we demonstrate that cetuximab treatment combined with immunostimulatory agonists for Toll-like receptor (TLR) 2 induces profoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Since death and severe cases of COVID-19 are associated with a hyper-inflammatory response [ 184 ], TLR2 antagonists can be tested for their capacity to alleviate the hyper-inflammatory response in SARS-CoV-2 infection or S protein stimulation. In addition, TLR2 has been demonstrated to be involved in the regulation of immune responses in autoimmune inflammatory diseases [ 185 , 186 ], kidney inflammaging [ 187 ], tissue injuries [ 71 , 188 ], gut microbiome dysbiosis [ 93 , 189 ], diabetes [ 11 ] and cancers [ 190 , 191 , 192 ].…”
Section: Therapeutic Targeting Of Tlr2 Signaling In Diseasesmentioning
confidence: 99%
“…Since death and severe cases of COVID-19 are associated with a hyper-inflammatory response [ 184 ], TLR2 antagonists can be tested for their capacity to alleviate the hyper-inflammatory response in SARS-CoV-2 infection or S protein stimulation. In addition, TLR2 has been demonstrated to be involved in the regulation of immune responses in autoimmune inflammatory diseases [ 185 , 186 ], kidney inflammaging [ 187 ], tissue injuries [ 71 , 188 ], gut microbiome dysbiosis [ 93 , 189 ], diabetes [ 11 ] and cancers [ 190 , 191 , 192 ].…”
Section: Therapeutic Targeting Of Tlr2 Signaling In Diseasesmentioning
confidence: 99%
“…In the article "NK Cell-Dependent Antibody-Mediated Immunotherapy Is Improved In Vitro and In Vivo When Combined with Agonists for Toll-like Receptor 2 in Head and Neck Cancer Models", Gruijs et al [6] investigated the effects of NK cell therapy combined with a Toll-like receptor (TLR) 2 agonist in a head and neck cancer model. The authors demonstrated that a cetuximab treatment, applied in combination with the immunostimulatory agonists of TLR 2, increased the release of several pro-inflammatory cytokines and chemokines by NK cells.…”
mentioning
confidence: 99%